Dynamics in the Predictability of Credit Default Swap Spreads of EU Companies - Kirill Romanyuk; Sarvar Anvarov; Mark Shumilov; Alecksey Zheleyko (Complexity)
The COVID-19 pandemic affected financial instruments and markets all around the world. Credit default swap contracts of EU companies were analysed in this paper. The data consist of daily credit default swap spreads and market capitalisations of EU companies, exchange rates, LIBOR rates, bond yields, and commodity futures prices from January 2010 to February 2022. The dynamics in the performance of forecasting models for credit default swap spreads before and after the declaration of the COVID-19 pandemic were measured by relative error metrics, i.e., relative root mean squared error, relative mean absolute error, and relative mean absolute percentage error. The results show a small drop in the performance right after the declaration of the COVID-19 pandemic that is mitigated by strong performance in the rest of the year, followed by a significant drop in the performance in the second year of the pandemic.